THU0374 NONSTEROIDAL ANTI-INFLAMMATORY DRUG-SPARING EFFECT OF SECUKINUMAB IN PATIENTS WITH ANKYLOSING SPONDYLITIS: 4-YEAR RESULTS FROM THE MEASURE 2, 3 AND 4 PHASE 3 TRIALS. (2nd June 2020) - Dougados, M.; Kiltz, U.; Kivitz, A.; Pavelka, K.; Rohrer, S.; Mccreddin, S.; Quebe-Fehling, E.; Porter, B.; Talloczy, Z.
Abstract : Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are effective in reducing pain and stiffness in ankylosing spondylitis (AS) patients (pts). 1 However, continuous use of NSAIDs may lead to gastrointestinal, cardiovascular and renal toxicity. 2 Therefore, reduction in NSAID intake is desirable in AS pts. Objectives: To evaluate the long-term effect of secukinumab (SEC) on NSAID intake in AS pts pooled from the 3 SEC trials (MEASURE [M] 2-4). Methods: NSAID intake was evaluated prospectively using the Assessment of SpondyloArthritis International Society (ASAS)-NSAID score. 3 The score was determined by type of NSAID, daily dose, and weights from frequency of intake, as well as % of time use in period. An ASAS-NSAID score of '0' indicates no NSAID intake. Pts with ASAS-NSAID score >0 at baseline (BL) were analysed. SEC dose groups were defined as Any 150 or 300 mg, as defined for pooled safety analyses for SEC. Pts with initial placebo treatment (up to 24 weeks) were included in their respective post-Week 24 SEC dose groups to analyse ASAS-NSAID score at Year (Y) 2 (M2-4), Y3 (M2-3) and Y4 (M2) from BL. From the ASAS-NSAID score at BL, the mean change in ASAS-NSAID score, proportion of pts achieving 50% reduction, and the proportion of pts with score <10 were evaluated for each dose at Y2, 3 and 4. Based on the distribution of ASAS-NSAID scores at BL, 2 subgroups were evaluated: (i) <75 (low user); (ii) ≥75 (high user). Results: Overall, 562 pts (SEC: 150 mg, N=467; 300 mg, N=95) were analysed. The mean ASAS-NSAID score decreased with time in both dose groups. Greater improvements were observed in high NSAID users and with longer treatment exposure (Figure ). Proportion of pts who achieved 50% reduction in ASAS-NSAID score increased with time in both SEC 150 and 300 mg groups. Proportion of pts with clinically meaningful reduction of ASAS-NSAID score <10 increased with time in both dose groups and in both low and high NSAID users (Table ). Conclusion: SEC provided sustained improvement in ASAS-NSAID score in AS pts and was associated with clinically relevant NSAID-sparing effect in AS pts, when used to measure NSAID intake up to 4 years of treatment. Overall, SEC provided long-term NSAID-sparing effects in both high and low NSAID users. References: [1]Molto A, et al. Joint Bone Spine . 2017;84:79–82. [2]Dougados M, et al. Arthritis Res & Ther . 2014;16:481. [3]Dougados M, et al. Ann Rheum Dis . 2011;70:249–51. Disclosure of Interests: Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Uta Kiltz Grant/research support from: AbbVie, Amgen, Biogen, Novartis, Pfizer, Consultant of: AbbVie, Biocad, Eli Lilly and Company, Grünenthal, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer, Roche, UCB, Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, , Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Karel Pavelka Speakers bureau: AbbVie, BMS, MSD, UCB, Medac, Egis, Pfizer, Roche, Biogen, Novartis, Susanne Rohrer Employee of: Novartis, Suzanne McCreddin Shareholder of: Novartis, Employee of: Novartis, Erhard Quebe-Fehling Shareholder of: Novartis, Employee of: Novartis, Brian Porter Shareholder of: Novartis, Employee of: Novartis, Zsolts Talloczy Shareholder of: Novartis, Employee of: Novartis